A polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures and its preparation method and application
By introducing sixteen flexible quaternary ammonium cations into the anion exchange membrane, the problems of low ion conductivity and poor chemical stability of the anion exchange membrane electrolytic water are solved, and higher ion conductivity and alkali resistance stability are achieved.
Patent Information
- Application Number
- CN202310062518.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-01-18
AI Technical Summary
The anion exchange membrane has low ion conductivity and poor chemical stability, making it difficult to maintain performance in an alkaline environment for a long time.
Using a polyarylether sulfone membrane material containing sixteen flexible quaternary ammonium cation structures, the introduction of sixteen quaternary ammonium cations into the polymer structural unit improves the motility of the ions and reduces the charge-induced effect between the cation and the framework structure.
It significantly improves the ion conductivity and stability of the membrane material, and can operate in alkaline water electrolytic cells for a long time and maintain good performance.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of high-performance anion exchange membranes for producing hydrogen by electrolysis of water and preparation thereof, and particularly relates to a polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures and a preparation method and application thereof. Background Art
[0002] The basic principle of water electrolysis is to use alkaline water as electrolyte and asbestos cloth, PPS cloth, etc. as diaphragm. After power is applied, H2O generates H2 and OH in the cathode area. - , OH - It enters the anode area through the diaphragm and generates O2 in the anode area. Currently, anion exchange membrane water electrolysis is coming into the sight of researchers. This technology uses anion exchange membrane instead of wet asbestos cloth for water electrolysis to produce hydrogen, which can effectively block the mixing of hydrogen and oxygen and improve the tolerance to pressure fluctuations on both sides of the membrane, so that intermittent and discontinuous power outputs such as wind power and photovoltaics can be directly used for water electrolysis to produce hydrogen. At the same time, the catalyst can use non-precious metal catalysts such as Ni, Co, and Fe that are similar to traditional alkaline liquid water electrolysis. Compared with the precious metal catalysts used in PEM water electrolysis, its cost will be greatly reduced.
[0003] At present, anion exchange membrane electrolysis is in the stage of research and development and improvement. As one of the most important components, the low ion conductivity and poor chemical stability of anion exchange membrane have always been a difficult problem that researchers have been committed to overcoming. Due to the difference in the conduction mechanism and the ion radius of the conduction, the conductivity of anion exchange membrane is much lower than that of proton exchange membrane. In addition, anion exchange membrane operates in an alkaline environment for a long time, and its ion groups and main chains are usually OH - The ion conductivity of anion exchange membrane materials is closely related to the distribution of ion aggregation and the linking mode, but due to the limitation of the synthesis method, it is difficult to introduce more than eight cations into the unit structure. The present invention provides a polyarylethersulfone anion exchange membrane containing sixteen flexible quaternary ammonium cations on a structural unit. The simultaneous introduction of flexible side chain structures improves the mobility of ions, reduces the charge induction effect between cations and the skeleton structure, and can further improve the ion conductivity and stability of the membrane material. Summary of the invention
[0004] The present invention provides a polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures, which has a structure of Formula 1; in Formula 1, the number of functionalized structural units is x, and each unit structure contains sixteen flexible quaternary ammonium cation structures, the number of non-functionalized structural units is y, x / (x+y)=0.14-0.22, and the molecular weight is generally 50-80. The value of x needs to take into account both high ion conductivity and dimensional stability. When x / (x+y)>0.22, the instability of the exchange membrane size and ion exchange performance will be caused by water absorption and swelling.
[0005]
[0006] The present invention also provides a method for preparing the polyarylethersulfone containing sixteen flexible quaternary ammonium cationic structures as described above, comprising: reacting the polyarylethersulfone containing multiple benzyl bromide structures shown in Formula 2 with the homemade 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide shown in Formula 3 to obtain the polyarylethersulfone containing sixteen flexible quaternary ammonium cationic structures shown in Formula 1.
[0007]
[0008] The specific preparation method is as follows: first, methyl iodide is added dropwise into N,N,N',N'-tetramethyl-1,6-hexanediamine.
[0009] Preferably, the reaction temperature of the above reaction is 40-80° C., and the reaction time is 4-6 hours.
[0010] Preferably, the organic solvent is tetrahydrofuran, and its usage is 5 to 10 times the mass of N,N,N',N'-tetramethyl-1,6-hexanediamine.
[0011] Preferably, the amount of N,N,N',N'-tetramethyl-1,6-hexanediamine used is 5 to 10 times that of methyl iodide.
[0012] Secondly, under nitrogen protection, a certain amount of polyarylethersulfone polymer containing eight benzyl bromide structures as shown in formula 2 is dissolved in an organic solvent, and then 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide is added. After the reaction is completed, the reactant is filtered and poured into a mold to obtain a polyarylethersulfone membrane containing sixteen quaternary ammonium cation structures as shown in formula 1.
[0013] Preferably, the reaction temperature of the above reaction is 50-80° C., and the reaction time is 10-16 h.
[0014] Preferably, the organic solvent is N-methylpyrrolidone or dimethyl sulfoxide, and the amount thereof is 30 to 60 times the mass of the polyarylethersulfone polymer containing the octabenzyl bromide structure.
[0015] Preferably, the amount of 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide used is 1 to 2 times the molar amount of benzyl bromide in the polyarylethersulfone polymer containing eight benzyl bromide structures.
[0016] Preferably, the polyarylethersulfone polymer containing eight benzylbromide structures is prepared according to the following steps: brominating the polyarylethersulfone containing eight methyl structures shown in formula 4 to obtain the polyarylethersulfone polymer containing multiple benzylbromide structures shown in formula 2.
[0017]
[0018] The specific preparation method is as follows: under nitrogen protection, a certain amount of polyarylethersulfone containing eight methyl structures as shown in formula 4 is dissolved in an organic solvent, benzoyl peroxide and N-bromosuccinimide are added, and the reaction is carried out at 60 to 85° C. for 6 to 8 hours, and the reactant is precipitated in hot ethanol to obtain a polyarylethersulfone polymer containing multiple benzyl bromide structures as shown in formula 2.
[0019] Further preferably, the organic solvent is 1,1,2,2-tetrachloroethane, and the amount used is 40 to 80 times the mass of the polyarylethersulfone polymer containing eight methyl structures; the amount of N-bromosuccinimide used is 2 to 3.5 times (more preferably 2 to 3 times) the molar amount of methyl groups in the polyarylethersulfone polymer containing eight methyl structures; the amount of benzoyl peroxide used is 5% to 9% of the molar amount of N-bromosuccinimide.
[0020] Preferably, the polyarylethersulfone containing eight methyl structures is prepared by the following method: 3,3',5,5'-tetrakis(3",5"-dimethylphenyl)-4,4'-difluorodiphenylsulfone, 4,4'-difluorodiphenylsulfone and 2,2-bis-(4-hydroxyphenyl)hexafluoropropane shown in Formula 5 are subjected to nucleophilic polycondensation reaction.
[0021]
[0022] The specific preparation method is as follows: under nitrogen protection, x parts of 3,3',5,5'-tetrakis(3",5"-dimethylphenyl)-4,4'-difluorodiphenyl sulfone shown in formula 5, 1-x parts of 4,4'-difluorodiphenyl sulfone and 1 part of 2,2-bis-(4-hydroxyphenyl)hexafluoropropane are added into a three-necked flask, and a proper amount of catalyst, organic solvent and dehydrating agent are added to carry out nucleophilic polycondensation reaction, and the reaction is carried out at 130-150° C. for 1-2 hours, followed by dehydration, and then the reaction is carried out at 170-180° C. for 4-8 hours to obtain the polyarylethersulfone containing eight methyl structures shown in formula 3.
[0023] Further preferably, the organic solvent is N-methylpyrrolidone, and its usage is 2 to 7 times the total mass of the three reaction monomers; the catalyst is potassium carbonate; its usage is 2 to 3 times the molar amount of 2,2-bis-(4-hydroxyphenyl)hexafluoropropane; the dehydrating agent is toluene, and its usage is 0.35 to 0.5 times the volume of N-methylpyrrolidone.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures provided by the present invention simultaneously introduces sixteen quaternary ammonium cation structures into the polymer structural unit to increase the aggregation degree of ionic functional groups, thereby further improving the ionic conductivity of the polymer membrane material; and further improves the alkali resistance and dimensional stability of the polymer membrane material by introducing benzene rings and flexible alkane chains to separate hydrophilic cations from the hydrophobic skeleton.
[0026] (2) The polyarylethersulfone polymer containing sixteen flexible quaternary ammonium cation structures provided by the present invention is prepared by the Menshutkin reaction and can be directly used to prepare ion exchange membranes by the tape casting method. The prepared ion exchange membranes have good ion conductivity, dimensional stability and chemical stability and can be used as ion exchange membrane materials in alkaline water electrolyzers for hydrogen production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a synthetic route for the polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures described in Example 1 of the present invention.
[0028] Figure 2 Middle a, Figure 2 Middle b, Figure 2 Medium c and Figure 3 This is the NMR spectrum of the polyarylethersulfone containing sixteen flexible quaternary ammonium cation structures and the intermediate product described in Example 2 of the present invention.
[0029] Figure 4 This is a graph of the ion conductivity of the polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures described in Examples 1, 2, and 3 of the present invention.
[0030] Figure 5 This is a graph showing the alkali resistance stability of the polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures described in Examples 1, 2, and 3 of the present invention.
[0031] Figure 6 This is a performance diagram of a water electrolyzer containing a polyarylethersulfone membrane material with sixteen flexible quaternary ammonium cation structures as described in Example 2 of the present invention. DETAILED DESCRIPTION
[0032] The present invention is further described in detail below in conjunction with embodiments:
[0033] The preferred embodiments of the present invention will be described in more detail below in conjunction with specific examples.
[0034] The sources of the drugs and reagents described in the examples are as follows:
[0035] N-Methylpyrrolidone: aladdin, ≥99.5%
[0036] Dimethyl sulfoxide: Shanghai Lingfeng Chemical Reagent Co., Ltd., ≥99.0%
[0037] Potassium carbonate: Shanghai Lingfeng Chemical Reagent Co., Ltd., ≥99.0%
[0038] 1,1',2,2'-Tetrachloroethane: Shanghai Lingfeng Chemical Reagent Co., Ltd., ≥99.0%
[0039] Benzoyl peroxide: aladdin, 90.0%
[0040] N,N,N',N'-Tetramethyl-1,6-hexanediamine: Anaiji Chemical, ≥98%
[0041] Iodomethane (CH3I): Anaiji Chemical, ≥98%
[0042] N-bromosuccinimide: Anaiji Chemical, 98%
[0043] 3,3',5,5'-Tetrakis(3",5"-dimethylphenyl)-4,4'-difluorodiphenyl sulfone: prepared according to reference (Journal of Membrane Science, 2015, 492, 281-288), 98%
[0044] 4,4'-Difluorodiphenyl sulfone: Great Wall Reagent, 98%
[0045] 2,2-Bis-(4-hydroxyphenyl)hexafluoropropane: Anaiji Chemical, 98%
[0046] Toluene: Sinopharm Chemical Reagent Co., Ltd., ≥99.5%.
[0047] Example 1
[0048] A method for preparing a polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures comprises the following steps:
[0049] (1) Preparation of poly(arylethersulfone) containing eight methyl groups
[0050] 0.9392 g (1.40 mmol) of 3,3',5,5'-tetrakis (3", 5"-dimethylphenyl)-4,4'-difluorodiphenyl sulfone, 2.1866 g (8.60 mmol) of 4,4'-difluorodiphenyl sulfone, 3.3623 g (10.00 mmol) of 2,2-bis-(4-hydroxyphenyl)hexafluoropropane, 2.7642 g (20.00 mmol) of K2CO3, 12 mL of N-methylpyrrolidone and 4 mL of toluene were added into a 100 mL three-necked flask with a stirrer, a water separator, a condenser and a N2 inlet and outlet. The mixture was first reacted at 145°C for 2 h, and then N2 was passed through to remove water and toluene. The temperature was then raised to 175°C for 5 h. The reaction solution was poured into ethanol for precipitation to obtain polyarylethersulfone (PAES-M-14) containing eight methyl structures with a yield of 89%.
[0051] (2) Preparation of polyarylethersulfone containing eight benzylbromide structures
[0052] In a 100mL three-necked flask equipped with a stirrer and N2 inlet and outlet, add 2.4000g (methyl content of 4.4153mmol) of polymethyl structure polyarylethersulfone (PAES-M-14) and 96mL of 1,1',2,2'-tetrachloroethane and stir until completely dissolved, then add 1.9646g (11.0382mmol) of N-bromosuccinimide and 0.2005g (0.8279mmol) of benzoyl peroxide, and react at 85°C for 7h. Pour the orange-red reaction solution into hot ethanol for precipitation to obtain polyarylethersulfone (PAES-Br-14) containing eight benzyl bromide structures with a yield of 82%.
[0053] (3) Preparation of 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide
[0054] A mixed solution of 17.2310 g (0.1000 mol) TMHDA and 100 mL THF was added to a 250 mL three-necked flask equipped with a stirrer and a N2 inlet and outlet, and 2.8388 g (0.0200 mol) CH3I was dissolved in 20 mL THF, and the mixed solution was slowly added dropwise to the three-necked flask through a constant pressure funnel, the temperature was adjusted to 60°C, and the reaction was terminated after stirring for 5 hours. The obtained turbid solution was filtered to obtain a white solid and dried in vacuo at 30°C, with a yield of 95%.
[0055] (4) Preparation of polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures
[0056] 0.6000 g (benzyl bromide content is 0.9639 mmol) of polyaryl ether sulfone polymer (PAES-Br-14) containing eight benzyl bromide structures was dissolved in 24 mL of dimethyl sulfoxide and added to a three-necked flask equipped with a stirrer and a N2 inlet and outlet. Then 0.3332 g (1.0603 mmol) of 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide was added to the three-necked flask, and the temperature was raised to 60°C. The reaction was continued for 12 hours. The reaction solution was filtered with a sand core funnel and poured into the prepared mold to obtain a polyaryl ether sulfone polymer membrane (PAES-MQA-0.14) containing multiple side chain tetramethylimidazolium structures with a yield of 96%.
[0057] The synthetic route of the above preparation method is as follows Figure 1 shown.
[0058] Example 2
[0059] A method for preparing a polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures, comprising the following steps
[0060] (1) Preparation of poly(arylethersulfone) containing eight methyl groups
[0061] 1.2075g (1.80mmol) 3,3',5,5'-tetrakis (3", 5"-dimethylphenyl) -4,4'-difluorodiphenyl sulfone, 2.0849g (8.20mmol) 4,4'-difluorodiphenyl sulfone, 3.3623g (10.00mmol) 2,2-bis- (4-hydroxyphenyl) hexafluoropropane, 2.7642g (20.00mmol) K2CO3, 12mL N-methylpyrrolidone and 4mL toluene were added into a 100mL three-necked flask with a stirrer, a water separator, a condenser and a N2 inlet and outlet. The mixture was first reacted at 145°C for 2h, then N2 was passed to remove water and toluene, and then the temperature was raised to 175°C for 6h. The reaction solution was poured into ethanol for precipitation to obtain poly (arylether sulfone) containing eight methyl structures (PAES-M-18) with a yield of 86%. 1 H NMR (DMSO-d6) as attached Figure 2 As shown in a.
[0062] (2) Preparation of polyarylethersulfone containing eight benzylbromide structures
[0063] In a 100mL three-necked flask equipped with a stirrer and N2 inlet and outlet, add 2.4000g (methyl content is 5.5255mmol) of polymethyl structure polyarylethersulfone (PAES-M-18) and 96mL of 1,1',2,2'-tetrachloroethane and stir until completely dissolved, then add 2.4586g (13.8138mmol) of N-bromosuccinimide and 0.2510g (1.0360mmol) of benzoyl peroxide, and react at 85°C for 7h. Pour the orange-red reaction solution into hot ethanol for precipitation, and obtain polyarylethersulfone (PAES-Br-18) containing eight benzyl bromide structures, with a yield of 87%. 1 H NMR (DMSO-d6) as attached Figure 2 As shown in b.
[0064] (3) Preparation of 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide
[0065] A mixed solution of 17.2310 g (0.1000 mol) TMHDA and 100 mL THF was added to a 250 mL three-necked flask equipped with a stirrer and a N2 inlet and outlet. Then 2.8388 g (0.0200 mol) CH3I was dissolved in 20 mL THF, and the mixed solution was slowly added dropwise to the three-necked flask through a constant pressure funnel. The temperature was adjusted to 60°C and the reaction was terminated after stirring for 5 hours. The obtained turbid solution was filtered to obtain a white solid and dried in vacuum at 30°C. The yield was 95%. 1 H NMR (DMSO-d6) as attached Figure 3 shown.
[0066] (4) Preparation of polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures
[0067] 0.6000 g (benzyl bromide content is 1.1691 mmol) of polyarylethersulfone polymer (PAES-Br-18) containing multiple benzyl bromide structures was dissolved in 24 mL of N-methylpyrrolidone and added to a three-necked flask equipped with a stirrer and a N2 inlet and outlet. Then 0.4041 g (1.2860 mmol) of 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide was added to the three-necked flask, and the temperature was raised to 60°C. The reaction was continued for 12 hours. The reaction solution was filtered with a sand core funnel and poured into a prepared mold to obtain a polyarylethersulfone polymer membrane (PAES-MQA-0.18) containing multiple side chain tetramethylimidazolium structures with a yield of 95%. 1 H NMR (DMSO-d6) as attached Figure 2 As shown in c.
[0068] Example 3
[0069] A method for preparing a polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures comprises the following steps:
[0070] (1) Preparation of poly(arylethersulfone) containing eight methyl groups
[0071] 1.4759 g (2.20 mmol) of 3,3',5,5'-tetrakis(3",5"-dimethylphenyl)-4,4'-difluorodiphenyl sulfone, 1.9832 g (7.80 mmol) of 4,4'-difluorodiphenyl sulfone, 3.3623 g (10.00 mmol) of 2,2-bis-(4-hydroxyphenyl)hexafluoropropane, 2.7642 g (20.00 mmol) of K2CO3, 15 mL of N-methylpyrrolidone and 5 mL of toluene were added into a 100 mL three-necked flask with a stirrer, a water separator, a condenser and a N2 inlet and outlet. The mixture was first reacted at 145°C for 2 h, and then N2 was passed through to remove water and toluene. The temperature was then raised to 175°C for 5 h. The reaction solution was poured into ethanol for precipitation to obtain polyarylethersulfone (PAES-M-22) containing multiple methyl structures with a yield of 84%.
[0072] (2) Preparation of polyarylethersulfone containing eight benzylbromide structures
[0073] In a 100mL three-necked flask equipped with a stirrer and N2 inlet and outlet, add 2.4000g (methyl content 6.5782mmol) of polymethyl structure polyarylethersulfone (PAES-M-22) and 96mL of 1,1',2,2'-tetrachloroethane and stir until completely dissolved, then add 2.9270g (16.4454mmol) of N-bromosuccinimide and 0.2988g (1.2334mmol) of benzoyl peroxide, and react at 85°C for 7h. Pour the orange-red reaction solution into hot ethanol for precipitation to obtain polyarylethersulfone (PAES-Br-22) containing multiple benzyl bromide structures with a yield of 85%.
[0074] (3) Preparation of 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide
[0075] A mixed solution of 17.2310 g (0.1000 mol) TMHDA and 100 mL THF was added to a 250 mL three-necked flask equipped with a stirrer and a N2 inlet and outlet, and 2.8388 g (0.0200 mol) CH3I was dissolved in 20 mL THF, and the mixed solution was slowly added dropwise to the three-necked flask through a constant pressure funnel, the temperature was adjusted to 60°C, and the reaction was terminated after stirring for 5 hours. The obtained turbid solution was filtered to obtain a white solid and dried in vacuo at 30°C, with a yield of 95%.
[0076] (4) Preparation of polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures
[0077] 0.6000 g (benzyl bromide content is 1.3521 mmol) of polyaryl ether sulfone polymer (PAES-Br-22) containing polybenzyl bromide structure was dissolved in 24 mL of N-methylpyrrolidone and added to a three-necked flask equipped with a stirrer and a N2 inlet and outlet. Then 0.4674 g (1.4874 mmol) of 6-(dimethylamino)-N,N,N-trimethylhexane-1-ammonium iodide was added to the three-necked flask, and the temperature was raised to 60°C. The reaction was continued for 12 hours. The reaction solution was filtered with a sand core funnel and poured into the prepared mold to obtain a polyaryl ether sulfone polymer membrane (PAES-MQA-0.22) containing sixteen quaternary ammonium cation structures with a yield of 92%.
[0078] The basic properties of the polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures obtained in the above example are shown in Table 1.
[0079] Table 1
[0080]
[0081] In the table: Test conditions: temperature is 80℃,
[0082] IEC Theo is the theoretical value;
[0083] IEC Tit Measured by titration;
[0084] WU% is the mass change of the membrane before and after water absorption;
[0085] SR% is the change in membrane length before and after water absorption;
[0086] σ was measured in pure water by an electrochemical workstation;
[0087] λ is the hydration number;
[0088] Ea is the activation energy.
[0089] It can be seen from Table 1 that the thickness of the prepared PAES-MQA-x membrane is Left and right, IEC Theo The theoretical design value is from 2.14 to 2.64mmol / g; IEC TitIt was measured by molar titration method, from 2.01 to 2.51mmol / g. The quaternary ammonium cation content per unit mass increases with the increase of IEC value, further promoting the conduction of ions, so the value of ionic conductivity σ increases with the increase of IEC value, and the ionic conductivity increases from 106.23mS / cm to 140.85mS / cm at 80°C; water absorption (WU) and swelling rate (SR) also increase with the increase of IEC value, and WU increases from 32.7% to 63.2% at 80°C, and SR increases from 12.9% to 18.6%.
[0090] The ionic conductivity of the membrane is one of the key factors in evaluating the performance of the membrane. The ionic conductivity of the PAES-MQA-x membrane was tested in the temperature range of 20°C to 80°C by the four-electrode method. Figure 4 As shown in the figure, the ionic conductivity of PAES-MQA-x membrane increases with the increase of IEC, and the increase of ion content is conducive to the improvement of conductivity. As water is a key carrier of ion conduction, the increase of its content promotes the ion diffusion rate. The increase of temperature makes the chain segment movement more intense, resulting in the increase of ionic conductivity with the increase of temperature.
[0091] When AEMs are assembled in a water electrolyzer, strong alkaline hydroxide ions are produced during the electrolysis process. Therefore, alkali resistance is one of the key properties to measure the performance of anion exchange membranes. This test takes PAES-MQA-0.18 membrane as an example and immerses it in 2 mol L -1 The membrane was immersed in a NaOH solution at 80°C for 480 h. The membrane's alkali resistance stability was evaluated by measuring the IEC and ionic conductivity of the membrane. Figure 5 As shown in the figure, IEC decreases with time, and its retention rate is 75.7% after 480h. The retention rate of ionic conductivity is 72.5% after 480h durability test.
[0092] Figure 6 The voltage durability curve of the battery is shown at 30°C and 2 mol L -1 NaOH solution as electrolyte, 500mAcm -2 The steady-state polarization curve was recorded for 480 h at a constant current density of . During the entire test, the voltage fluctuated between 1.71 V and 1.76 V. The overall test shows the feasibility of this type of membrane operating under alkaline conditions.
[0093] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Without departing from the scope and technical principles of the described embodiments, many modifications and changes are obvious to those of ordinary skill in the art, and these modifications and changes should also be regarded as the scope of protection of the present invention.
Claims
1. A polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures, characterized in that: The structural formula is: Formula 1, In Formula 1, the number of functionalized structural units is x, and each unit structure contains sixteen flexible quaternary ammonium cation structures, and the number of non-functionalized structural units is y, x / (x+y)=0.14~0.
22.
2. The method for preparing the polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures according to claim 1, characterized in that: The method comprises the following steps: reacting a polyarylethersulfone having eight benzyl bromide structures as shown in formula 2 with 6-dimethylamino- N, N,N -trimethylhexane-1-ammonium iodide to obtain a polyarylethersulfone having a sixteen-membered flexible quaternary ammonium cation structure as shown in Formula 1; Formula 2.
3. The method for preparing the polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures according to claim 2, characterized in that: The method also includes the following steps: firstly, under nitrogen protection, pouring polyarylethersulfone containing eight benzylbromide structures into a reaction container and dissolving it with an organic solvent, and then adding 6-dimethylamino- N,N,N -Trimethylhexane-1-ammonium iodide is added to a reaction container and stirred to react. After the reaction is completed, it is filtered and then poured into a mold for drying to obtain a polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures as shown in Formula 1.
4. The method for preparing the polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures according to claim 3, characterized in that: The organic solvent is dimethyl sulfoxide, the reaction temperature is 50-80°C, and the reaction time is 10-16 hours.
5. The method for preparing the polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures according to claim 2, characterized in that: The 6-dimethylamino- N,N,N The preparation method of trimethylhexane-1-ammonium iodide comprises the following steps: adding methyl iodide dropwise to N,N,N',N' -Tetramethyl-1,6-hexanediamine, the solvent is tetrahydrofuran, N,N,N', N' The amount of tetramethyl-1,6-hexanediamine used is 5 to 10 times that of methyl iodide, the reaction temperature is 40 to 80 °C, the reaction time is 4 to 6 h, and the reaction formula is as shown in Formula 3: Formula 3.
6. The method for preparing the polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures according to claim 2, characterized in that: The 6-dimethylamino- N,N,N The amount of trimethylhexane-1-ammonium iodide used is 1 to 2 times the molar amount of benzyl bromide in the polyarylethersulfone containing eight benzyl bromide structures.
7. The method for preparing the polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures according to claim 2, characterized in that: The preparation method of the polyarylethersulfone containing eight benzylbromide structures comprises the following steps: brominating the polyarylethersulfone containing eight methyl structures shown in formula 4 to obtain the polyarylethersulfone containing eight benzylbromide structures shown in formula 2; Formula 4.
8. The method for preparing the polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures according to claim 7, characterized in that: The preparation method of the polyarylethersulfone polymer containing eight benzylbromide structures also includes the following steps: dissolving the polyarylethersulfone containing eight methyl structures described in formula 4 in an organic solvent, then adding an initiator and a brominating agent in sequence, pouring into ethanol for sedimentation after the reaction is completed, filtering and drying, and then obtaining the polyarylethersulfone polymer containing eight benzylbromide structures as shown in formula 2.
9. The method for preparing the polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures according to claim 8, characterized in that: The organic solvent used in the preparation of the polyarylethersulfone polymer containing eight benzyl bromide structures is 1,1,2,2-tetrachloroethane, and its dosage is 30 to 60 times the mass of the polyarylethersulfone with eight methyl structures; the brominating agent is NBS, and its dosage is 2.0 to 3.5 of the molar amount of the methyl group; the initiator is BPO, and its dosage is 5% to 9% of the molar amount of NBS. The reaction temperature is 60 to 85°C, and the polyarylethersulfone polymer containing eight benzyl bromide structures can be obtained.
10. The use of the polyarylethersulfone membrane material containing sixteen flexible quaternary ammonium cation structures according to claim 1, characterized in that: Used in alkaline water electrolyzers to produce hydrogen.
Citation Information
Patent Citations
Polyether sulphone containing plurality of quaternary ammonium salt phenyl side group structures and preparation method for polyether sulphone
CN104861167A
Tertiary amine type polyarylether sulfone (ketone) polymer resin and preparation method and anion-exchange membrane thereof
CN110294845A